THE ANALYSIS OF ARTIFICIAL INTELLIGENCE (AI) USAGE PHENOMENA IN ONLINE DISCUSSIONS OF ECONOMIC EDUCATION STUDENTS - Lodya Sesriyani; Sri Rahayu (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2026)
ABSTRACT The rapid integration of Artificial Intelligence (AI) in the higher education ecosystem poses new challenges to the originality of thought and students' cognitive processes. While AI offers efficiency, its unregulated use has the potential to degrade critical inquiry skills, particularly in courses demanding a profound understanding of human behavior. This study aims to analyze the phenomenon of AI usage among second-semester students in the Economic Education Study Program, specifically within the "Human Development" course. A descriptive qualitative approach with a case study design was employed. Data were collected from 32 discussion transcripts on the Mentari platform and validated through time-stamp analysis and in-class cross-verification (member checking). The findings reveal that 87.5% of students utilized AI to complete their discussion assignments, characterized by high linguistic homogeneity, formal-synthetic syntax, and a lack of contextual reflection. Empirical evidence shows a significant "knowledge-wisdom gap," where students produce sophisticated text without conceptual mastery. The study concludes that AI dependency at UNPAM has created an "academic facade," shifting the learning process from reflective inquiry to automated task completion. It is recommended that lecturers redesign discussion prompts into "AI-proof" assignments that prioritize local context and personal reflection to restore pedagogical integrity in the digital era. Keywords: artificial intelligence; development of learners; economic education; mentari unpam; online learning ABSTRAK Pesatnya integrasi Artificial Intelligence (AI) dalam ekosistem pendidikan tinggi membawa tantangan baru terhadap orisinalitas pemikiran dan proses kognitif mahasiswa. Meskipun AI menawarkan efisiensi, penggunaannya yang tidak teregulasi berpotensi mendegradasi kemampuan inkuiri kritis, terutama dalam mata kuliah yang menuntut pemahaman mendalam mengenai perilaku manusia. Penelitian ini bertujuan untuk menganalisis fenomena penggunaan AI di kalangan mahasiswa semester dua Program Studi Pendidikan Ekonomi, khususnya pada mata kuliah "Perkembangan Peserta Didik". Pendekatan kualitatif deskriptif dengan desain studi kasus digunakan dalam penelitian ini. Data dikumpulkan dari 32 transkrip diskusi di platform Mentari dan divalidasi melalui analisis time-stamp serta verifikasi silang di dalam kelas (member checking). Temuan menunjukkan bahwa 87,5% mahasiswa menggunakan AI untuk menyelesaikan tugas diskusi mereka, yang ditandai dengan homogenitas linguistik yang tinggi, sintaksis formal-sintetis, dan kurangnya refleksi kontekstual. Bukti empiris menunjukkan adanya celah pengetahuan-kebijaksanaan (knowledge-wisdom gap) yang signifikan, di mana mahasiswa menghasilkan teks yang canggih tanpa penguasaan konsep. Penelitian menyimpulkan bahwa ketergantungan pada AI di UNPAM telah menciptakan fasad akademik, mengubah proses belajar dari inkuiri reflektif menjadi penyelesaian tugas otomatis. Disarankan agar dosen merancang ulang instruksi diskusi menjadi tugas yang tahan AI (AI-proof) dengan memprioritaskan konteks lokal dan refleksi personal untuk memulihkan integritas pedagogis di era digital. Kata Kunci:​ artificial intelligence; mentari unpam; pembelajaran daring; pendidikan ekonomi; perkembangan peserta didik